Studentų žinių įverčių statistinė analizė - Krylovas, Aleksandras; Suboč, Olga; Kosareva, Natalja (Lietuvos matematikos rinkinys, 2021)
Students’ knowledge of discrete mathematics was tested using two methods – ‘close-type’ test and ‘inwriting’. ‘In-writing’ was independently evaluated by two different teachers. These results were statistically analyzed in this article.